Digital resilience interventions for healthcare workers: a systematic review - Larsson, Malin; Ho, Dominic M.; Kirschner, Matthias; Seifritz, Erich; Manoliu, Andrei (Frontiers in Psychiatry, 2025)
IntroductionBurnout among healthcare professionals is rising, exacerbated by increased workloads and the Covid-19 pandemic. Affected individuals face stress, depression, and anxiety, adversely impacting both personal well-being and patient care. Resilience has emerged as a key focus for targeted interventions, with online delivery gaining relevance due to the digital transformation and the need for flexibility in busy healthcare schedules.MethodsA systematic review was conducted by searching PubMed, Embase, and Web of Science for eligible studies from April 2014 to April 2024, using search terms related to resilience, online/blended interventions, and healthcare professionals. A total of 7,619 records were identified and screened by two independent reviewers (ML, AM). Final inclusion was based on predefined criteria for online or blended interventions aimed at enhancing resilience in healthcare professionals. The Effective Public Health Practice Project (EPHPP) assessed risk of bias. PRISMA guidelines were followed.ResultsFifty-five studies were selected, employing various interventions such as psychoeducation, meditation, mindfulness, and elements of cognitive-behavioral therapy (CBT) and acceptance and commitment therapy (ACT). Interventions were delivered online through websites, apps, audio files, etc. or in blended formats complementing in-person sessions. Most studies reported significant improvements in resilience, alongside reductions in stress, burnout, depression, and anxiety. However, only three studies in the online group involving mindfulness or CBT interventions received a strong global rating in the risk of bias assessment by fulfilling the methodological quality criteria. Among these, mindfulness, compared to a waitlist control or a psychoeducational brochure, significantly improved resilience and reduced burnout, while the CBT intervention, compared to bibliotherapy, led to a significant reduction in stress. Compared to the other studies, these three stood out due to minimal selection bias, low attrition rates, a robust study design, and at least partial blinding.DiscussionThis review indicates that digital interventions may enhance resilience and associated factors in healthcare personnel. However, caution is advised due to the heterogeneity of interventions and varied measurement methods. Only three studies met methodological quality criteria, limiting the reliability of other findings. Future research should standardize resilience concepts and adhere to methodological criteria to ensure valid conclusions.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024542758 PROSPERO, identifier CRD42024542758.